Asymptomatic versus symptomatic patients: [18F]FDG-PET/CT patterns and evolutionary track of COVID-19 associated vasculitis - Martina Sollini; Fabrizia Gelardi; Arturo Chiti (Verduci Editore, 2021)
Several patients experience unexplained persistent symptoms after recovering from severe acute respiratory syndrome-related coronavirus disease 2 (SARS-CoV-2) [the so-called long coronavirus disease (COVID)], with a negative impact on their quality of life. We report the evolutionary track of fluorine-18-fluorodeoxyglucose positron emission tomography-computed tomography ([18F]FDG-PET/CT) in two patients incidentally diagnosed with SARS-CoV-2 infection. In both cases, baseline PET/CT showed bilateral pneumonia associated with [18F]FDG vascular uptake. Vascular uptake was more evident in the baseline scan of the asymptomatic patient. Vice versa, it was more marked in the follow-up examinations of the patient who developed long COVID. These findings suggested that vascular inflammation and its duration are responsible for the clinical course of the disease and the development of long COVID.